Attractiveness of beach resort models for formal and informal commerce : a comparative study between Patong Beach and Laguna Phuket, Thailand. - Ng, Guan Ling. (2009)
The dichotomy of formal and informal sectors and the operational constraints faced when operating within a beach resort are examined in the context of a comparative study of Patong Beach, an ad hoc beach resort, and Laguna Phuket, an integrated beach resort, both in Phuket, Thailand.